You better watch out - Murray, James S. (James Stephen), 1976-; Wearmouth, Darren (St. Martin's Press, 2024)
"From international bestselling authors James S. Murray (better known as "Murr" on the hit TV show Impractical Jokers) and Darren Wearmouth, comes You Better Watch Out, a suspenseful, serial killer thriller that leaves you wondering, is Christmas really the best time of the year? Forty-eight hours until Christmas, Jessica Kane wakes up with blurred vision, ears ringing, and in excruciating pain. A gash in her head and blood running down her face, the last thing she remembers is going for a run and something or someone hitting her in the head. It doesn't take her long to realize she is trapped in an unknown, deserted town with five other strangers who share similar stories of being attacked and stranded there. Unsure why and how they got there, she knows one thing for certain, she has to find a way out. That becomes nearly impossible when someone is meticulously orchestrating their deaths, one by one, and the only thing Jessica can do is watch the life leave their eyes. The fenced-in town is the killer's very own playground and there's nowhere left to hide... she better watch out because she could be next"--